Programme Instrumental Theory as a Principle of Thinking of the Performer (The Case of Musical Compositions for the Solo Flute of Chinese Composers of the Twentieth Century) - Yang Li (Культура України, 2019)
The aim of the paper is concerned with the programme instrumental theory in the flute art as a principle of thinking of the performer that is embodied in composer’s attitude toward the flute and the comprehension of timbre possibilities of the flute in single works. Research methodology. The offered paradigm of studying the programme instrumental theory in the flute art makes it possible to connect aesthetic and culturological, genre and stylistic approaches in the context of musicological method. Results. The specific character of art thinking of the performer reveals the world-modeling, semantic, timbre-coloristical and time-spatial parameters of musical sound. The author determines the main historical and culturological and immanent stylistic factors of the flute performance as a unity of composer’s and performing creation, as the co-operation of academic and non-academic options of the flute instrumentalism. Novelty. The analysis of traditional and innovative repertoire of the flutist achieves a stylistic and textological level and enables to line up the conception of “flute instrumentalism” as a theory and practically meaningful for a modern flutist — performer and teacher. The unity of performing and musicological issues is confirmed in the course of musical message. Certain performing ways are revealed in the context of artistic and stylistic bases of the flute performance. The practical significance. The key results can be used in the lectures of performing skills, as well as in the series of lectures «Music Culture of Foreign Countries». Keywords: flute, programme music, instrumental theory, principles of art thinking, genre, style.